Kajian in silico Penghambatan Spesifik 3C-like Protease SARS-CoV-2 Senyawa Quinic Acid, Gluconic Acid, dan Ferulic Acid pada Kulit Kopi - Yohanes Bare; Frederiksen Novenrius Sini Timba; Dewi Ratih Tirto Sari; Oktavius Yoseph Tuta Mago; Maria Marcelina Dua Nurak (Jurnal Ilmiah Medicamento, 2022)
This study aims to explore the chemical compounds of the coffee pulp as an anti-covid-19 (anti-3C-like protease). In silico modeling was carried out by structure retrieval, protein preparation, and docking simulation. Specific Grid docking was used for ligands – protein interacting by using Molegro Virtual Docker 5, followed by visualizing Discovery studio version 21.1.1. Compounds contained in coffee pulp, quinic acid, gluconic acid, and ferulic acid separately bind to the same amino acid residues of 3CL Protease or each other. Furthermore, three compounds inhibited 3CLPro activity by catalytic site blocking of 3CLPro, indicating that coffee compounds have potential as molecular therapeutic materials for the coronavirus by inhibiting SARS-CoV-2 genome replication.